Preoperative RAS Mutational Analysis Is of Great Value in Predicting Follicular Variant of Papillary Thyroid Carcinoma - Hwang, Tae Sook (Biomed Res Int, 2015)
Follicular variant of papillary thyroid carcinoma (FVPTC), particularly the encapsulated subtype, often causes a diagnostic dilemma. We reconfirmed the molecular profiles in a large number of FVPTCs and investigated the efficacy of the preoperative mutational analysis in indeterminate thyroid nodules. BRAF V600E/K601E and RAS mutational analysis was performed on 187 FVPTCs. Of these, 132 (70.6%) had a point mutation in one of the BRAF V600E (n = 57), BRAF K601E (n = 11), or RAS (n = 64) genes. All mutations were mutually exclusive. The most common RAS mutations were at NRAS codon 61. FNA aspirates from 564 indeterminate nodules were prospectively tested for BRAF and RAS mutation and the surgical outcome was correlated with the mutational status. Fifty-seven and 47 cases were positive for BRAF and RAS mutation, respectively. Twenty-seven RAS-positive patients underwent surgery and all except one patient had FVPTC. The PPV and accuracy of RAS mutational analysis for predicting FVPTC were 96% and 84%, respectively. BRAF or RAS mutations were present in more than two-thirds of FVPTCs and these were mutually exclusive. BRAF mutational analysis followed by N, H, and KRAS codon 61 mutational analysis in indeterminate thyroid nodules would streamline the management of patients with malignancies, mostly FVPTC.